An Endometrial Thickness < 8 mm Was Associated With a Significantly Increased Risk of EP After Freeze-Thaw Transfer: An Analysis of 5,960 Pregnancy Cycles - Zhao, Ying; Liu, Dong’e; Liu, Nenghui; Li, Yumei; Yao, Zhongyuan; Tian, Fen; Xu, Aizhuang; Li, Yanping (Frontiers in Endocrinology, 2022)
Introduction: Endometrium characteristics which are most likely to induce ectopic pregnancy were investigated based on the data of 5,960 pregnant freeze-thaw cycles. Methods: A total of 5,960 pregnancy cycles after freeze-thaw embryos transfer were included, with the number of intrauterine and ectopic pregnancies being 5,777 and 183 respectively. Ectopic pregnancy was the primary outcome. Endometrial thickness was the main measured variable. The risk factors of ectopic pregnancy were eventually determined based on univariate analysis and subsequent multiple-stepwise logistic regression analysis. Results: 1. After adjusting for confounders, endometrial thickness could independently predict ectopic pregnancy. The adjusted odd ratios for women with endometrial thickness in the ranges of < 8 mm, 8–9.9 mm, and 10-11.9 mm were 3.270 (95% confidence interval [CI], 1.113-9.605, P= 0.031), 2.758 (95% CI, 0.987-7.707, P= 0.053) and 1.456 (95% CI, 0.502-4.225, P= 0.489), respectively, when compared with those having an endometrial thickness of 12-13.9mm. 2. Endometrial type and preparation protocol were however not identified as risk factors for ectopic pregnancy. Discussion: 1. After freeze-thaw embryo transfer, risks of ectopic pregnancy were significantly higher when the endometrial thickness was < 8mm. 2. A thin endometrial thickness could be linked with abnormal endometrial peristaltic waves or abnormal endometrial receptivity. 3. Adequate attention should therefore be paid to patients with a thin endometrial thickness to prevent EP or to achieve early diagnosis during the peri-transplantation period.